Acute symptoms during the course of head and neck radiotherapy or chemoradiation are strong predictors of late dysphagia. Issue 1 (April 2015) - van der Laan, Hans Paul; Bijl, Hendrik P.; Steenbakkers, Roel J.H.M.; van der Schaaf, Arjen; Chouvalova, Olga; Vemer-van den Hoek, Johanna G.M.; Gawryszuk, Agata; van der Laan, Bernard F.A.M.; Oosting, Sjoukje F.; Roodenburg, Jan L.N.; Wopken, Kim; Langendijk, Johannes A.
Abstract: Purpose: To determine if acute symptoms during definitive radiotherapy (RT) or chemoradiation (CHRT) are prognostic factors for late dysphagia in head and neck cancer (HNC). Material and methods: This prospective cohort study consisted of 260 HNC patients who received definitive RT or CHRT. The primary endpoint was grade 2–4 swallowing dysfunction at 6 months after completing RT (SWALM6). During treatment, acute symptoms, including oral mucositis, xerostomia and dysphagia, were scored, and the scores were accumulated weekly and entered into an existing reference model for SWALM6 that consisted of dose–volume variables only. Results: Both acute xerostomia and dysphagia were strong prognostic factors for SWALM6. When acute scores were added as variables to the reference model, model performance increased as the course of treatment progressed: the AUC rose from 0.78 at the baseline to 0.85 in week 6. New models built for weeks 3–6 were significantly better able to identify patients with and without late dysphagia. Conclusion: Acute xerostomia and dysphagia during the course of RT are strong prognostic factors for late dysphagia. Including accumulated acute symptom scores on a weekly basis in prediction models for late dysphagia significantly improves the identification of high-risk and low-risk patients at an early stage during treatment and might facilitate individualized treatment adaptation.